Soil properties as constraints to seedling regeneration beyond alpine treelines in the Canadian Rocky Mountains. Issue 1 (1st January 2018) - Davis, Emma L.; Hager, Heather A.; Gedalof, Ze'ev
ABSTRACT: Plants growing at the edges of their range limits are expected to be particularly sensitive to changes in precipitation and temperature regimes associated with climatic change. However, non-climatic factors are increasingly recognized as important constraints to species' range expansions. Therefore, we assessed the effects of soil provenance with respect to the alpine treeline on the germination, growth, and survival of Engelmann spruce ( Picea engelmannii ) seedlings. Seedlings were grown under controlled conditions in a growth chamber and greenhouse for ninety days in soils collected from four treeline ecotones in the Canadian Rocky Mountains. By controlling seed source and climatic conditions, and eliminating competition and predation, we attribute differences in seedling viability to soil properties that differed across elevation zones and individual treeline sites. Overall, alpine soils originating from beyond the species' current elevational range were least amenable to growth, and there was some indication of reduced germination and survival in high-elevation soils. Forest soils, which were coarser and more nutrient rich, hosted seedlings with greater above- and below-ground biomass. Thus, the physical and chemical characteristics of alpine soils in our study region may constrain future treeline expansion, underscoring the importance of incorporating soil properties when considering species' distributions under climate change.